Self-care practices among type 2 diabetes mellitus patients in rural India - Shivananda, Richitha; Savkar, Madhav K.; Manchukonda, Ravi Shankar; Krishnegowda, Raghavendra Srirangapura (International Journal of Basic & Clinical Pharmacology, 2020)
Background: The prevalence of diabetes mellitus (DM) has been increasing all over the world in past 30 years, particularly in the Indian subcontinent with an estimated 87% diabetic population within the age group 20-70 years. The increase in severity of diabetes every year has been linked to patient’s lack of knowledge and practice of self-care. Hence educating the population as well as assessing their self-care practices has become important. Methods: A cross-sectional study with 253 participants was done using the diabetic self-management questionnaire (DSMQ). Socio demographic details were also collected along with the questionnaire. The questionnaire was scored reversing the negatively worded questions (with a minimum score of 10 to maximum score of 34) and the p values and Pearson’s correlation was used to determine the significance of factors like age and gender with self-care practices. Results: Among 253 subjects, 117 (46.2%) participants felt that their self-care practices were poor to a ‘considerable extent’, hence the self-care practices of type 2 DM in rural population was poor and factors like age and gender didn’t show any significance in overall self-care of type 2 DM. Conclusions: The self-care practices of type 2 DM patients in rural area is poor. Age and gender had no significance in the self-care practices of type 2 DM patients. Hence awareness programs should be done in order to educate the rural population about the importance of self-care in dealing with the complications of diabetes.